Freedom from Religion and Its Legal Impact in Indonesia - Ichsan, Muchammad; Prasetyoningsih, Nanik (International Journal of Psychosocial Rehabilitation, 2019)
The population of Indonesia is made up of several ethnicities and cultures. It is therefore not surprising that they also have different kinds of religions and beliefs. Some of them have no religion at all. The aim of this study is to examine whether Indonesian law allows people to have no faith or not. In addition, this study outlines the legal impact of anti-religion in Indonesia.For these purposes this analysis is intended to be qualitative and to use normative legal research methods. Research has shown that there are religious freedom laws in Indonesia.People are entitled to follow whatever religion they want, especially the six official religions, namely Islam, Christianity, Catholicism, Buddhism, Hinduism, and Confucianism.They also have the right to worship in accordance with the teachings of their faith. Nevertheless, according to a strong opinion, the right to recognize any religion does not mean the freedom not to be religious. Thus, Indonesia prohibited atheism based onseveral arguments. Indigenous belief, though not a religion, is not atheism. Indigenous belief is justified and has legal protection in Indonesia since it has been there for a long time. The legal consequence for those who do not have a religion is that they will face difficulties in obtaining their rights, on example in the case of education marriage and finance.